(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
In this article, the authors present dogmas about the importance of sleep for the body of athletes, where it is a natural physiological process in which the entire body is updated, the restoration of physical and mental strength. The sleep of professional athletes is important for restoring the energy costs of the body, as well as for the normal functioning of all organs and systems, therefore, high-quality sleep is necessary to achieve high sports results. The article analyzes scientific information about the representation, nature and consequences of its violations, summarizes and structured data regarding the strategy of optimizing sleep in qualified athletes.